Guest Editoral: Science And Friction in Orthodontics - Geenty J. P. (Sciendo, 1995)
"The real gulf is not the gap between the Arts and Sciences but the canyon between those who practice genuine scientific thinking (whether or not they have a scientific background) and everyone else, including many scientists and engineers highly trained in narrow specialties."